The Use of The Lingodeer Application in Enhancing Students’ Vocabulary Mastery - Hasanah, Nur; Ulfa, Siti Maria (STKIP PGRI Ponorogo Press, 2024)
This research aims to reveal the implementation and responses of students using the Lingodeer application as a medium used by students to find students' vocabulary gains after they use the Lingodeer application in class 7B of SMPN 01 Konang trough a qualitative research. The Lingodeer applicationwas chosen because it provides a variety of interactive and engaging language learning features, which can be accessed by students anytime and anywhere. The research method used is a case study with data collection trough field note observation, interview, and documentation.The result showed that students who used the Lingodeer Application in enhance students’ vocabulary. Observation during teaching and learning activities showed that students were more enthusiastic and active in the learning process. interview with students revealed that they felt more motivated and interested in learning English using the Lingodeer application because of the interactive and fun learning medium. Documentation also supports this finding, showing an enhance in the number of vocabulary words that students mastered after using this application. This research concludes that Lingodeer application is effective in enhancing students’ vocabulary and can be a useful tool for teachers in teaching English. It is recommended that teachers consider using learning applications like Lingodeer to create a more dynamic and effective learning experiencenext research could explore the use of this application in other language skills as well as its long-term effects on students’ language proficiency